Stimulus representations in visual cortex shaped by spatial attention and microsaccades - Karthik Srinivasan; Eric Lowet; Bruno Gomes; Robert Desimone (Proceedings of the National Academy of Sciences, 2025)
Microsaccades (MSs) are commonly associated with covert spatial attention, yet their impact on cortical processing of visual objects remains unclear. Rhesus macaques, randomly cued to attend to a target object amid distracters, were rewarded for detecting a color change in the target. While spatial attention does not affect the object tuning curves of V4 cells, the direction of MS significantly influenced object representations in V4 throughout the entire trial. Specifically, intervals following an MS toward the target exhibited superior stimulus decoding and sharper tuning curves compared to intervals following an MS away from the target. Furthermore, MSs directed toward the target enhanced neuronal responses to behaviorally relevant color changes, leading to faster reaction times. This sharpening effect stems from both a refreshing of the initial sensory response and an amplification of attention effects. The firing rate enhancement associated with spatial attention is delayed until the occurrence of the first MS directed toward the target. Subsequently, a positive effect of attention on firing rate, influenced by MS direction, was found throughout the trial across deep and superficial layers of V4, lateral pulvinar, and IT cortex. In summary, these findings underscore a crucial link between covert attention, object processing, and their coordination with MSs.